Irradiation damage in GaAs particle detectors - Brozel, M.R. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 1997)
GaAs particle detectors for use in the LHC at CERN will be subject to a considerable fluence of energetic particles. In this note, possible effects of this irradiation on the production of damage centres in these detectors will be discussed.